Holistic-Integrative Early Childhood Development in the Full Day Program at Integrated ECE Bakti Baitussalam - Puji Dwi Rahayu (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2020)
This research aimed to determine the program, implementation and supporting and inhibiting factors for the holistic-integrative early childhood development (ECD-HI) in the full day program at Bakti Baitussalam Integrated Early Childhood Education. This research used descriptive research with a qualitative approach. This research examined and explored the development of a holistic-integrative early childhood in the full day program at Integrated ECE Bakti Baitussalam. This research examined what happened, there was no special treatment to the subject, but seeing the subject and object as they are. To get an overview of the processes/events that occurred in the field, the researchers conducted observations, interviews and analyzed existing documents related to holistic- integrative early childhood development in the full day program at Integrated ECE Bakti Baitussalam. The results of this research included: 1) The Holistic-Integrative Early Childhood Development Program (ECD-HI,) The Full Day Program at Integrated ECE Bakti Baitussalam consists of routine programs, support programs, and special service programs; 2) The implementation of ECD-HI program in Integrated ECE Bakti Baitussalam was carried out through learning activities, religious activities,  extracurricular activities, parenting activities, doctor examination activities, child consultation and DDT;  3) The factors that supported ECD--HI at Integrated ECE Bakti Baitussalam were the character and quality of educators, while the inhibiting factors were limited facilities and infrastructure such as APE, less optimal teacher cooperation.